## How Do You Expand \( (x-1)^3 \)?

You can Expand \( (x-1)^3 \) through formulas and simple multiplication method.

first of all, I am going to expand \( (x-1)^3 \) through the formula.

\( (a-b)^3 = a^3+3ab^2–3a^2b–b^3 \)

\( (x-1)^3 = x^3+3 \times x \times 1^2–3\times x^2 \times 1–1^3 \)

\( (x-1)^3 = x^3+3x – 3x^2 –1 \)

Now, I am going to expand \( (1-x)^3 \) through the Multiplication.

\( (x-1)^3 = (x-1)^2 (x-1) \)

\( (x-1)^3 = (x^2+1 – 2x) (x-1) \)

\( (x-1)^3 = x(x^2+1 – 2x) – 1 (x^2+1 – 2x) \)

\( (x-1)^3 = (x^3+x – 2x^2) – (x^2+1 – 2x) \)

\( (x-1)^3 = x^3+x – 2x^2 – x^2-1+ 2x \)

\( (x-1)^3 = x^3+3x – 3x^2 -1 \)

Expand Form of \( (x-1)^3 = x^3+3x – 3x^2 -1 \)